2012
DOI: 10.7748/ns.26.51.44.s55
|View full text |Cite
|
Sign up to set email alerts
|

Myeloproliferative neoplasms: diagnosis, management and treatment

Abstract: This article provides an overview of myeloproliferative neoplasms for nurses who do not specialise in haematology. Diagnosis, management and treatment of patients with these conditions is discussed, as well as long-term nursing implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Apart from that, it is reported that chemokines and cytokines produced by inflammatory reaction cause genetic instability, leading to the occurrence and development of tumors, and play an important role in the pathogenesis of Ph-MPNs. 44 Therefore, it is reasonable to confirm that infection plays an important role in the development of thrombotic events in patients with Ph-MPNs. In this study, patients with various age, sex, and blood cell showed no significant difference in the occurrence of thrombotic events, which showed that PAI-1 gene 4G/5G polymorphism and infection were related to thrombotic events.…”
Section: Discussionmentioning
confidence: 96%
“…Apart from that, it is reported that chemokines and cytokines produced by inflammatory reaction cause genetic instability, leading to the occurrence and development of tumors, and play an important role in the pathogenesis of Ph-MPNs. 44 Therefore, it is reasonable to confirm that infection plays an important role in the development of thrombotic events in patients with Ph-MPNs. In this study, patients with various age, sex, and blood cell showed no significant difference in the occurrence of thrombotic events, which showed that PAI-1 gene 4G/5G polymorphism and infection were related to thrombotic events.…”
Section: Discussionmentioning
confidence: 96%
“…Arterial thrombosis, the direct cause of cardiovascular events, is the main risk factor affecting the survival of MPN patients ( 25 ). Thromboembolism-related mortality accounts for 35%–70% of the total mortality of MPN ( 26 ), with ACS being the common one ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, as far as the cases of venous thrombosis are concerned, only the male sex was found to be significantly linked to these events [30]. The relationship between thrombosis and leukocytosis, thrombosis and JAK2V617F6, or pregnancy-associated complications and JAK2V617F has been examined by different groups of investigators with conflicting and inconclusive results [31][32][33].…”
Section: • Low Risk (Absence Of Both Risk Factors)mentioning
confidence: 99%